Working and learning together: good quality care depends on it, but how can we achieve it? - McPherson, K (BMJ Group, 2001)
Educating healthcare professionals is a key issue in the provision of quality healthcare services, and interprofessional education (IPE) has been proposed as a means of meeting this challenge. Evidence that collaborative working can be essential for good clinical outcomes underpins the real need to find out how best to develop a work force that can work together effectively. We identify barriers to mounting successful IPE programmes, report on recent educational initiatives that have aimed to develop collaborative working, and discuss the lessons learned. To develop education strategies that really prepare learners to collaborate we must: agree on the goals of IPE, identify effective methods of delivery, establish what should be learned when, attend to the needs of educators and clinicians regarding their own competence in interprofessional work, and advance our knowledge by robust evaluation using both qualitative and quantitative approaches. We must ensure that our education strategies allow students to recognise, value, and engage with the difference arising from the practice of a range of health professionals. This means tackling some long held assumptions about education and identifying where it fosters norms and attitudes that interfere with collaboration or fails to engender interprofessional knowledge and skill. We need to work together to establish education strategies that enhance collaborative working along with profession specific skills to produce a highly skilled, proactive, and respectful work force focused on providing safe and effective health for patients and communities. Key Words: interprofessional education; multiprofessional learning; teamwork